227k views
1 vote
-18 + 2a = 2(3a + 1)

2 Answers

6 votes

Answer:

-5

Explanation:

User BoJack Horseman
by
5.2k points
3 votes

Answer:

a = -5

Explanation:

Given

-18 + 2a = 2(3a + 1)

Expand the bracket on the right

-18 + 2a = 2 x 3a + 2 x 1

-18 + 2a = 6a + 2

Add 18 to both sides

-18 + 18 + 2a = 6a + 2 + 18

2a = 6a + 20

Subtract 6a from both sides

2a - 6a = 6a - 6a + 20

-4a = 20

Divide both sides by -4

-4a/-4 = 20/-4

a = -5

User Maxime
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.